The influence of workload and burnout syndrome on turnover awareness moderated by perception of organizational support (At KJPP Sugianto Prasodjo and colleagues) - Syafira Zatil Aqmar; Fauzi Sanusi; Ali Imron (PT. Hasba Edukasi Mandiri, 2025)
This research aims to examine the effect of workload suitability and burnout syndrome on turnover intention, with perceived organizational support as a moderating variable at KJPP Sugianto Prasodjo dan Rekan. The population of this study consists of 200 employees, with the sample including 200 employees of KJPP Sugianto Prasodjo dan Rekan, selected using purposive sampling. Data analysis was performed using PLS-SEM, with hypothesis testing carried out in two stages: testing the outer model and the inner model. The outer model test was conducted to assess the validity and reliability of all indicators for each variable, while the inner model test was performed to evaluate the relationships between variables based on the predefined hypotheses. The results indicate that workload suitability has a positive and significant effect on turnover intention, burnout syndrome also has a positive and significant effect on turnover intention, and perceived organizational support is capable of moderating both the effect of workload and burnout syndrome on turnover intention.